O problema da distanásia à luz da discussão bioética atual - Leite, Elisabete dos Santos (2021)
This dissertation consists of an introductory presentation on "the problem of dysthanasia in the light of the current bioethical discussion", a specific theme of biomedical ethics. The analysis begins by exposing the context of medicine that, due to significant scientific advances, death is no longer a natural outcome and has become an enemy that must be overcome at any cost. The main objective of the research is to clarify what are the possible solutions in the case of moral dilemmas of dysthanasia. The most important discussion was the question about: to what extent can the doctor stay only on the basis of a deontological morality to define the best moral choice and what is the role of emotions for a truly moral action? The exhibition follows the following steps: As a point of reference, I analyze the perspective of the old deontological ethics in contrast to the new bioethical propedeutics, from a historical and conceptual contextualization of the central issues of bioethics, medical ethics and hypocratic ethics. I intend to show the different meanings or perspectives of a series of systematic questions that at first glance seems to suggest a discussion of practical questions of the application of certain rules, but it is not so easy to decide which reasons and criteria guarantee a certain form application, a concrete medical practice of a moral character. Second, I analyze philosophically the technoscientific, commercial-business and humanitarian paradigms as a way to better understand dysthanasia. Third, I present the fundamental perspective of current bioethics with an exposition of the new biomedical ethics and the relativization of hypocratic morals. Finally, even though there is still great difficulty in defining answers in this new perspective of bioethical investigation, I concluded by the need to respect the patient's right to autonomy, with emphasis on the substantial or evaluative aspects surrounding empathic engagement in the doctor-patient relationship.